Thyroid disease in patients with idiopathic thrombocytopenic purpura (Health Renaissance, 2012)
Idiopathic thrombocytopenia (ITP) is an autoimmune disorder characterized by a reduced platelet count with otherwise normal blood cell counts. Autoimmune thyroid disease is not considered a cause of thrombocytopenia. We report a case of autoimmune thrombocytopenic purpura associated with hyperthyroidism in which the patient's thrombocytopenia and thyrotoxicosis resolved concomitantly. We recommend testing for hyperthyroidism in all patients with unexplained thrombocytopenia and that family members of patients be evaluated, screened, and observed for thrombocytopenia and hyperthyroidism. Health Renaissance; September-December 2012; Vol 10 (No.3);254-255DOI: http://dx.doi.org/10.3126/hren.v10i3.7058